Repercussões da pandemia de Covid-19 na saúde mental das crianças e suas famílias em contexto de adversidades - Araújo, Antônia Kaliny Oliveira de (2023)
The pandemic had important repercussions on different Brazilian childhoods, with consequences for the health and well-being of this population, especially as those with greater social vulnerability and those with chronic illnesses and/or psychiatric disorders. A presentation of stressful, challenging and unpredictable life events such as the COVID-19 pandemic, increased or risk of psychological distress in children and serious caregivers. This study aimed to measure the repercussions of the COVID-19 pandemic on the mental health of children assisted at a Child Psychosocial Care Center - CAPSi in Fortaleza, Ceará. This is a cross-sectional, quantitative and analytical study, with 150 participants (boys and girls aged 6 to 12 years) residing in the State of Ceará in the territories of regions II, IV and VI. Data collection took place from August to December 2022, and respondents were mothers or caregivers who lived with the child. The electronic data management tool was REDCap1, hosted at the Clinical Research Unit of the UFC University Hospital Complex. In the analysis of the characteristics of the participants so that they are used or tested by Mann-Whitney, tested by Student, ANOVA and Kruskall-Wallis. In investigating the association between categorical variables, Pearson's chi-square test, Wilcoxon rank sum test and Fisher's exact test were used. The results indicated a significant value on the perception of worsening in children's mental health during a pandemic. In the same period, 81% of children adopted violent behaviors with (p <0.001), 49% of children intentionally hurt themselves (p = 0.004), 60% of children worried about having bad feelings and thoughts (p <0.001), 83% of patients adopted negative changes in their routine (p = 0.002) and 65% of children complained about not spending time with friends (p = 0.002). Therefore, the study indicates evidence of the changes that occurred during the pandemic with consequences for the lives of children and their families, indicating emotional and psychic instability, effects on routine, damage to family and social coexistence, failures and deficiencies in mental health care for mothers and caregivers. Thus, it can be inferred that this care process, which benefits pediatric and very family patients, still faces many challenges in public health, explaining a scenario of illness that is still little recognized.